Insights of curricular supervised intership for geography teacher academic training - Lira Júnior, Fernando César Rocha (Geosaberes, 2017)
The intership is essential in the formation of any professional, in teacher academic trainig is the moment of contact with the school. This is a reflection on the insights of the Curricular Supervised Intership of  geography teachers academic traning, whereas: laws, conceptions and our experiences around the theme. The general objective is to analyze the contributions of internships. In the specific objectives, intended to identify those laws about the stage; understand the main conceptions of interships along the history of the formation of teachers; reflect on our experiences with the stages, while otherwise commissioning of the course of Geography - UFC. Bibliographical surveys were made about the legislation of the interships, the decade of 40 until 2008. Besides bibliographical searches on the concepts of stage, which have their dichotomy placed before/after the decade of 1990. Were taken in consideration the probationary reports (I, II, III and IV) as a record of our experiences. We conclude that the laws are inadequacies about the activity of intership and need of supervision. Designed as a moment to reflect on teacher praxis, the stage is rich in experiences and reflections on the future teaching profession and the development of technical skills and research.
Keywords: Formação Docente em Geografia; Estágio Supervisionado; Legislação, Concepções e Experiências.